No Regional Gray Matter Atrophy Differences between Pediatric‐ and Adult‐Onset Relapsing‐Remitting Multiple Sclerosis. Issue 1 (14th January 2013) - Donohue, Katelyn; Cox, Jennifer L.; Dwyer, Michael G.; Aliotta, Rachel; Corwin, Melanie; Weinstock‐Guttman, Bianca; Ann Yeh, E.; Zivadinov, Robert
ABSTRACT OBJECTIVE To investigate differences in region‐specific gray matter (GM) damage between adults with pediatric‐onset (PO) multiple sclerosis (MS) and adult‐onset (AO) MS. METHODS Twenty‐four relapsing‐remitting (RR) adults with POMS (mean age = 35 years, mean disease duration = 18.4 years) were compared to 23 age‐matched (AOA, mean age = 33.9 years, mean disease duration = 2.4 years) and 24 disease‐duration matched (AOD, mean age = 45.9 years, mean disease duration = 18.5 years) RRMS adults who developed MS after the age of 18. Three‐dimensional‐T1‐weighted images were acquired on a 1.5 T MRI. Image analysis was conducted using voxel‐based morphometry (Statistical Parametric Mapping 8). RESULTS There were no regional GM atrophy differences between POMS and AODMS groups. No regional GM atrophy differences were found between POMS and AOAMS patients when disease duration was included as a covariate. CONCLUSIONS Regional GM differences were not found between POMS adults and MS controls matched for age or disease duration. Although of limited sample size, these findings suggest that there are no regional GM atrophy differences between RR POMS and AOMS.